Keefektifan Pembelajaran Realistic Mathematic Education dan Media Audiovisual terhadap Kemampuan Representasi Matematis Siswa SDN 10 Petarukan - Rahmadani, Dhiva; Trimurtini, Trimurtini (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2025)
This study aims to determine the effectiveness of Realistic Mathematic Education (RME) learning and audiovisual media on the mathematical representation abilities of elementary school students. The background of this study is the importance of mastering mathematical representation in mathematics learning and the need for contextual and interesting learning models for students. This study uses a quantitative approach with a quasi-experimental design in the form of a nonequivalent control group design. The subjects of the study were fifth grade students at SDN 10 Petarukan, with class 5A as the control class and 5B as the experimental class. The instruments used were pretest and posttest questions developed based on indicators of mathematical representation abilities. The results of the data analysis showed that there was an increase in the average value of student learning outcomes in the experimental class compared to the control class. However, the results of statistical tests (hypothesis tests and Z tests) showed that the increase was not statistically significant and did not meet the criteria for classical completeness. Although it has not shown significant effectiveness, this shows that RME learning and audiovisual media have the potential to improve students' mathematical representation abilities. More intensive and sustainable implementation is needed so that this model can provide a more optimal and significant impact.